2024
DOI: 10.37978/tijfs.v5i1.312
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tranexamic Acid in reducing intra-operative bleeding during tonsillectomy

Abstract: Background: Our study aims to determine the effectiveness of tranexamic acid in decreasing the intraoperative blood loss during tonsillectomy. Materials and Methods: Study design was randomized double-blind control trial.  This study was conducted from 1 November 2017 till 30 June 2019 in the department of ENT unit-II, the civil sandeman provincial teaching hospital Quetta. Ethical approval was taken from Ethical Review Board of the civil Sandeman provincial teaching hospital Quetta. A sample of 100 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…[23][24][25]30 Santosh et al 23 reported a mean reduction of 40.72 mL in their study group while George et al 24 reported a reduction of 29.68 mL. Achakzai et al 30 similarly reported a reduction of 29.59 mL in their study group. Pukhlik et al 29 reported a much lower reduction at 19 mL.…”
Section: Intraoperative Bleedingmentioning
confidence: 93%
See 3 more Smart Citations
“…[23][24][25]30 Santosh et al 23 reported a mean reduction of 40.72 mL in their study group while George et al 24 reported a reduction of 29.68 mL. Achakzai et al 30 similarly reported a reduction of 29.59 mL in their study group. Pukhlik et al 29 reported a much lower reduction at 19 mL.…”
Section: Intraoperative Bleedingmentioning
confidence: 93%
“…[23][24][25]29,30 Four out of these five studies reported significant reduction in the volume of intraoperative blood loss. [23][24][25]30 Santosh et al 23 reported a mean reduction of 40.72 mL in their study group while George et al 24 reported a reduction of 29.68 mL. Achakzai et al 30 similarly reported a reduction of 29.59 mL in their study group.…”
Section: Intraoperative Bleedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the NOS, all non-randomized studies 17,18,20,22,23,26 received a score between 6 and 8, indicating that they had fair methodological quality (Table 4). Most of the RCTs 19,21,24,25 had a low risk of bias (Figure 2), except for the study conducted by Castelli and Vogt 25 due to poor blinding of participants and personnel.…”
Section: General Characteristics and Methodological Quality Of Studiesmentioning
confidence: 99%